Investment Behaviour and Firms' Financial Performance: A Comparative Analysis Using Firm-Level Data from the Wine Industry - Claudiu Tiberiu Albulescu (International School for Social and Business Studies, 2020)
This paper assesses the role of financial performance in explaining firms' investment dynamics in the wine industry from the three European Union (EU) largest producers. The wine sector deserves special attention to investigate firms' investment behaviour given the high competition imposed by the latecomers. More precisely, we investigate how the capitalisation, liquidity and profitability influence the investment dynamics using firm-level data from the wine industry from France (331 firms), Italy (335) firms and Spain (442) firms. We use data from 2007 to 2014, drawing a comparison between these countries, and relying on difference- and system-GMM estimators. Specifically, the impact of profitability is positive and significant, while the capitalisation has a significant and negative impact on the investment dynamics only in France and Spain. The influence of the liquidity ratio is negative and significant only in the case of Spain. Therefore, we notice different investment strategies for wine companies located in the largest producer countries. It appears that these findings are in general robust to different specifications of liquidity and profitability ratios, and to the different estimators we use.